Effects of advanced footwear technology on running economy and endurance performance: a meta-analysis - Xiao, Y.; Hu, X.; Tian, D.; Qiu, A. (International Journal of Sports Medicine, 2025)
This study aimed to evaluate the effects of advanced footwear technology (AFT) on running economy (RE) and endurance performance. A systematic search was conducted on Web of Science, PubMed, Cochrane Library, and Embase databases on February 9, 2025, using the search terms "advanced footwear technology," "running economy," and "running." Main effect sizes were calculated using Hedges` g, and meta-analyses were performed using R Studio. A total of 17 randomized crossover trials with a total of 281 participants were included. Results showed that AFT significantly reduced oxygen consumption (VO2) [g=-0.44, 95% confidence interval (CI):-0.59,-0.30, p<0.001], energy cost (EC) (g=-0.35, 95% CI:-0.48,-0.22, p<0.001), and the cost of transport (g=-0.39, 95% CI:-0.65,-0.14, p<0.01) compared to conventional running shoes. Subgroup and regression analyses indicated that improvements in VO2 (ß=-0.041, p=0.200) and EC (ß=-0.025, p=0.436) were inversely related to running speed, with higher speeds associated with greater improvements in RE. Additionally, AFT improved time trial performance (g=-0.23, 95% CI:-0.37,-0.10, p<0.001). These findings suggest that AFT offers a moderate advantage in improving running efficiency, and it can help athletes achieve faster times in competitive settings.